2009
DOI: 10.1016/j.visres.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-fine dichotomies in human stereopsis

Abstract: There is a long history of research into depth percepts from very large disparities, beyond the fusion limit. Such diplopic stimuli have repeatedly been shown to provide reliable depth percepts. A number of researchers have pointed to differences between the processing of small and large disparities, arguing that they are subserved by distinct neural mechanisms. Other studies have pointed to a dichotomy between the processing of 1st- and 2nd-order stimuli. Here we review literature on the full range of dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 61 publications
1
86
0
1
Order By: Relevance
“…These IA settings are quite large-much larger than would normally be used to film such a scene in typical film industry practice (disparities of the poles were never divergent). It is well established that as disparity increases beyond an upper limit, depth percepts plateau and eventually decrease [Wilcox and Allison 2009]. …”
Section: Resultsmentioning
confidence: 99%
“…These IA settings are quite large-much larger than would normally be used to film such a scene in typical film industry practice (disparities of the poles were never divergent). It is well established that as disparity increases beyond an upper limit, depth percepts plateau and eventually decrease [Wilcox and Allison 2009]. …”
Section: Resultsmentioning
confidence: 99%
“…However, sensitivities to these large disparities have been shown to primarily reflect matching of temporally abrupt contrast envelopes, with little or no contributions of the orientation-specific information within the envelopes (Wilcox & Allison, 2009). In contrast, our pseudoplaid Gabor elements were presented with gradual temporal onsets and within stationary envelopes.…”
Section: Discussionmentioning
confidence: 99%
“…Later research revealed subtleties in the way this information is used. Ogle (1952a, 1952b, 1953) 1956;Mitchell, 1966a;Blakemore, 1970;Siderov and Harwerth, 1993;Wilcox and Allison, 2009), showing the processes to be tolerant to great differences in content between the stimuli presented to each eye (Mitchell, 1969), and how they are grounded in neurophysiology (Poggio and Fischer, 1977;Neri, 2005).…”
Section: Double Images and Depth Perceptionmentioning
confidence: 99%
“…Later research revealed subtleties in the way this information is used. Ogle (1952a, 1952b, 1953) 1956;Mitchell, 1966a;Blakemore, 1970;Siderov and Harwerth, 1993;Wilcox and Allison, 2009), showing the processes to be tolerant to great differences in content between the stimuli presented to each eye (Mitchell, 1969), and how they are grounded in neurophysiology (Poggio and Fischer, 1977;Neri, 2005).The visual system can also generate stereopsis from scenes when a nearer object occludes a further object such that one eye sees part of the scene that is not available to the other -a phenomenon first noted by Leonardo da Vinci and now known as ‗da Vince Stereopsis ' (Nakajama and Shimojo, 1990). These so-called unpaired images Despite our being largely unaware of their appearance in everyday visual experience, doubled or unpaired images are a rich source of information about the spatial properties of the world we see.…”
mentioning
confidence: 99%